Dynamics of brain derived neurotrophic factor when using neuromodulation as part of comprehensive rehabilitation after a stroke - Khramtsov, D. (Journal of Education, Health and Sport, 2025)
The aim of the study was to assess the dynamics of brain derived neurotrophic factor when using neuromodulation. Material and methods. The study was conducted on the basis of clinical departments of the Medical Institute of the Petro Mohyla Black Sea National University. 140 patients with ischemic stroke were treated. The total sample was randomly divided into 4 clinical groups. Patients in group I (n=30) received standard therapy, which included antithrombotic therapy, antihypertensive drugs, statins, and, according to indications, NSAIDs, antiemetics, insulin and other hypoglycemic drugs, antidepressants, etc. Patients in group II (n=40) received peptidergic compounds (cerebrolysin 40 ml per day) in the acute and long-term periods (a month after discharge). Patients in group III (n=40) received traditional therapy with transcranial micropolarization of the brain. In patients of group IV (n=30) it was used combined neuroprotection in the acute and long-term periods (peptidergic compounds in combination with brain micropolarization). The level of Brain-Derived Neurotrophic Factor (BDNF) was determined using the enzyme-linked immunosorbent assay (Sigma-Aldrich kit RAB0026, USA) during hospitalization and after 3, 6 and 12 months. The study was performed in compliance with modern bioethical requirements. All patients signed an informed consent to participate in the study. Statistical analysis performed using analysis of variance using the software Statistica 14.1.25 (TIBCO, USA). Patients with ischemic stroke were characterized by a decrease in serum BDNF concentration to 10.1±0.3 ng/ml. In all clinical groups, the indicator increased later, with the most pronounced dynamics observed in patients of group IV. In group I the increment was +44.6%, in group II - +68.3%, in group III - +56.4%, and in group IV - +79.2% with maximum approximation to the reference values. Conclusions: 1. The use of neuromodulation has a positive effect on the synthesis of neurotrophins. 2. The positive effect of neuromodulation is long-lasting